Level of knowledge among coronary artery bypass grafting patients in Hospital Universiti Sains Malaysia - Mansor, Norshuhada Murad@ (Universiti Sains Malaysia, 2009)
Preoperative education has a positive impact on cardiac patient's increase level of knowledge. It helps to prepare patient physically and psychologically, since the patient undergoing coronary artery bypass grafting (CABG) has a hard time maintaining the health status after the surgery. The objective of this study is to explore the knowledge outcome of the patient regarding basic cardiac, lifestyle, and myocardial infarction risk factor among CABG patients. Besides, the paper would like to determine the relationship of sociodemographic data (sex, marital status) with knowledge level of CABG patients. This is a descriptive and quantitative study. This study took place in Cardiothoracic Intensive Care Unit (CICU) and Surgery Clinic (SOPD), HUSM. The self-administered questionnaire was provided to patients (n=13) during post-CABG phase. Patients has a low cardiac knowledge with mean score of 59.23 (mean score <70). This included the basic cardiac knowledge (89.90±13.20), knowledge on lifestyle were found at low level with men score of 62.86±14.83, and myocardial infarction risk factor knowledge with low level mean score of 39.42±17.56. There is no association between both sex and marital status with cardiac health knowledge. In conclusion, CABG patient's knowledge is low especially in lifestyle and risk factor despite the preoperative intervention. Thus, ways to improvise the preoperative should be taken to produce positive effect upon cardiac health knowledge of patient.